Analiza tehnicko-taktiskih aktivnosti rukometasica na svjetskom prvenstvu 2019 godine - Karalic, T. (Sports Science and Health, 2020)
The subject of the research is the evaluation of the competitive performance of the female handball players senior level, with an emphasis on the diff erences in the competitive activities of successful and less successful teams at the 2019 World Handball Championship held in Japan. The aim was to determine the level of effi ciency of competitive activity of female handball players and the diff erences in the performance of a competitive activity, which potentially exist between successful and less successful handball teams, from the aspect of technical and tactical activities in the attack phase. The sample is represented by the female handball national teams that participated in the recently held Handball World Cup, and the entities are handball matches. The procedures of descriptive and comparative statistics were applied. The conclusion is that, regardless of the top level of handball playing, there are signifi cant diff erences in the realization of some competitive activities among successful and less successful female national teams. It was also found that the coeffi cient of efficiency of technical and tactical elements, in numerical sense, determines the success of most handball teams at this level of competition, and that there are diff erences, in the statistical sense, for 3 of the 7 variables designated as variables characteristic of the attack phase, from who success is directly achieved, respectively, the goals are achieved.